2022
DOI: 10.1037/edu0000672
|View full text |Cite
|
Sign up to set email alerts
|

How you read affects what you gain: Individual differences in the functional organization of the reading system predict intervention gains in children with reading disabilities.

Abstract: There is now considerable evidence regarding the types of interventions that are effective at remediating reading disabilities on average. It is generally unclear, however, what predicts the magnitude of individual-level change following a given intervention. We examine new predictors of intervention gains that are theoretically grounded in computational models of reading and focus on individual differences in the functional organization of the reading system. Specifically, we estimate the extent to which chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…Among these opportunities are: examining the causes of individual differences in learning to read; understanding the key pressure points in learning to read (such as transitions from monosyllabic to polysyllabic reading); predicting the impacts of different interventions on children's learning; and discovering how learning may vary across different languages and writing systems. The gap between behavioural and computational studies can then be narrowed through future behavioural work that specifies more closely the cognitive mechanisms involved in children's language task performance (e.g., Siegelman, Rueckl, van den Bunt, Frijters, Zevin, Lovett, Seidenberg, Pugh & Morris, 2022), together with increasingly detailed computational modelling that gets closer to children's language experience, and the constraints on their perception and production of language.…”
Section: Discussionmentioning
confidence: 99%
“…Among these opportunities are: examining the causes of individual differences in learning to read; understanding the key pressure points in learning to read (such as transitions from monosyllabic to polysyllabic reading); predicting the impacts of different interventions on children's learning; and discovering how learning may vary across different languages and writing systems. The gap between behavioural and computational studies can then be narrowed through future behavioural work that specifies more closely the cognitive mechanisms involved in children's language task performance (e.g., Siegelman, Rueckl, van den Bunt, Frijters, Zevin, Lovett, Seidenberg, Pugh & Morris, 2022), together with increasingly detailed computational modelling that gets closer to children's language experience, and the constraints on their perception and production of language.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have investigated the variability in reading behaviors among typical readers (Hoffman et al, 2015;Woollams et al, 2016;Davies et al, 2017;Siegelman et al, 2020Siegelman et al, , 2022Chang, 2023) and dyslexic readers (Ziegler et al, 2008;Perry et al, 2019). Particularly, inter-subject variability in efficient OP and OS mapping sensitivity has been considered critical in contributing to variations in reading performance (Hoffman et al, 2015;Woollams et al, 2016;Siegelman et al, 2020Siegelman et al, , 2022. For instance, Woollams et al (2016) examined how individual differences in the degree to which readers rely on semantic access affect reading performances in a reading-aloud task.…”
Section: Individual Differences In Readingmentioning
confidence: 99%
“…To become a proficient reader, children need to learn the mappings between orthography (O), semantics (S), and phonology (P). Past literature has shown that reading behaviors differ across readers as a function of their sensitivity to OP and OS mappings during reading (Hoffman et al, 2015;Woollams et al, 2016;Siegelman et al, 2020Siegelman et al, , 2022. Moreover, these individual differences may be critical factors that influence the OPEN ACCESS EDITED BY Maria Mody, Massachusetts General Hospital and Harvard Medical School, United States effectiveness of reading instruction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations